Numerical Simulation of a Pitching Airfoil Under Dynamic Stall of Low Reynolds Number Flow - Mojtaba Honarmand; Mohammad Hassan Djavareshkian; Behzad Forouzi Feshalami; Esmaeil Esmaeilifar (Journal of Aerospace Technology and Management, 2019)
In this research, viscous, unsteady and turbulent fluid flow is simulated numerically around pitching NACA0012 airfoil in the dynamic stall area. The Navier-Stokes equations are discretized based on the finite volume method and are solved by the PIMPLE algorithm in the open-source software, namely OpenFOAM. The SST k –w model is used as the turbulence model for Low Reynolds Number flows in the order of 105. A homogenous dynamic mesh is used to reduce cell skewness of mesh to prevent non-physical oscillations in aerodynamic forces, unlike previous studies. In this paper, the effects of Reynolds number, reduced frequency, oscillation amplitude and airfoil thickness on aerodynamic force coefficients and dynamic stall delay are investigated. These parameters have a significant impact on the maximum lift, drag, the ratio of aerodynamic forces and the location of dynamic stall. The most important parameters that affect the maximum lift to drag coefficient ratio and cause dynamic stall delaying are airfoil thickness and reduced frequency, respectively.